2020
DOI: 10.3389/fpsyg.2020.571961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Unexpected and Expected Event on Older Adults’ Autonomic Arousal and Eye Fixations During Autonomous Driving

Abstract: Driving cessation for some older adults can exacerbate physical, cognitive, and mental health challenges due to loss of independence and social isolation. Fully autonomous vehicles may offer an alternative transport solution, increasing social contact and encouraging independence. However, there are gaps in understanding the impact of older adults' passive role on safe human-vehicle interaction, and on their well-being. 37 older adults (mean age ± SD = 68.35 ± 8.49 years) participated in an experiment where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 70 publications
0
6
0
3
Order By: Relevance
“…Theus, the perception level of the driver was improved where it is conducive to increasing the response ability and making preparation for taking over the autonomous vehicle. Stephenson et al [40] found that the skin conductance level of drivers increased after triggering the takeover request, indicating that the drivers' perception was aroused. To sum up, after the takeover request is triggered, the perception level of drivers will increase.…”
Section: Discussionmentioning
confidence: 99%
“…Theus, the perception level of the driver was improved where it is conducive to increasing the response ability and making preparation for taking over the autonomous vehicle. Stephenson et al [40] found that the skin conductance level of drivers increased after triggering the takeover request, indicating that the drivers' perception was aroused. To sum up, after the takeover request is triggered, the perception level of drivers will increase.…”
Section: Discussionmentioning
confidence: 99%
“…A viselkedési horgonyok közül első a Technológiai Én-hatékonyság, második az Észlelt külső kontroll, harmadik a Technológiai szorongás, negyedik pedig a Technológia játékossága (Strauch et al, 2019). A korrekciós tényezők az észlelt élvezeti érték, és az objektív használhatóság (Stephenson et al, 2020).…”
Section: Bevezet é Sunclassified
“…Stephenson et al also explored older adults' autonomic arousal and found that safety-critical events (such as TORs) may narrow their visual attention and elevate arousal mechanisms (Stephenson et al, 2020). Furthermore, increasing the level of automation does not seem to decrease driving performance; on the contrary, it may even provide a safer drive among drivers with limited experience with the technology (Weaver et al, 2020).…”
Section: Related Work On To Quality Aspectsmentioning
confidence: 99%